Systematic assessment of triticale‐based biorefinery strategies: market competitive analysis for business model development. (31st August 2018) - Téguia, Cédric Diffo; Chambost, Virginie; Stuart, Paul R
Abstract: Triticale (X Triticosecale Wittmack) is a high‐productivity cereal crop that holds great promise as an industrial feedstock for agricultural biorefineries, as it can grow on marginal lands. Several product derivatives can be envisioned; however, they need to be systematically explored and assessed using a sustainability perspective, in order to define a business model that would lead to a long‐term competitive position. This study presents a competitive analysis of triticale‐based product‐process alternatives defined on ethanol, polylactic acid (PLA), and thermoplastic starch polymer blends (TPS/PLA) product platforms. As part of the analysis framework, we sought to identify a set of important market‐oriented criteria for multi‐criteria decision‐making (MCDM), prior to an overall sustainability assessment in which techno‐economic and environmental criteria are considered as well. From an initial set of necessary competitiveness criteria, three 'most‐important' competitiveness criteria for the sustainability assessment of the PLA platform were identified including competitive access to biomass, competitiveness on production costs, and the potential to manage market price volatility. Certain key factors have been highlighted for each platform as an outcome of the competitiveness assessment, such as the impact of value‐added co‐products on the competitive position of commodity‐based product portfolios, and the advantage of combining grain and straw process lines for specialty‐based product portfolios leading to improved competitive potential. © 2018 Society of Chemical Industry and John Wiley & Sons, Ltd